2015
DOI: 10.1371/journal.pone.0143603
|View full text |Cite
|
Sign up to set email alerts
|

Oral Microbiota and Risk for Esophageal Squamous Cell Carcinoma in a High-Risk Area of China

Abstract: Poor oral health has been linked with an increased risk of esophageal squamous cell carcinoma (ESCC). We investigated whether alteration of oral microbiota is associated with ESCC risk. Fasting saliva samples were collected from 87 incident and histopathologicallly diagnosed ESCC cases, 63 subjects with dysplasia and 85 healthy controls. All subjects were also interviewed with a questionnaire. V3–V4 region of 16S rRNA was amplified and sequenced by 454-pyrosequencing platform. Carriage of each genus was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
169
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(179 citation statements)
references
References 37 publications
6
169
1
3
Order By: Relevance
“…Other studies have characterized the microbiota related to ESCC (13) and its precursor, ESD (12). Yu et al observed that lower microbial richness and altered composition of upper digestive tract microbiota were associated with ESD in Chinese subjects (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have characterized the microbiota related to ESCC (13) and its precursor, ESD (12). Yu et al observed that lower microbial richness and altered composition of upper digestive tract microbiota were associated with ESD in Chinese subjects (12).…”
Section: Discussionmentioning
confidence: 99%
“…The complex microbial community of the upper digestive tract, consisting of mutualists, commensals, and pathogens, could facilitate carcinogenesis via activation of toll-like receptors (6), or protect against carcinogenesis via synthesis of vitamins or providing barriers to pathogen invasion (5). Cross-sectional studies report distinct differences in upper digestive tract microbiota between GERD (79), Barrett’s esophagus (BE, an EAC precursor) (710), EAC (7,11), esophageal squamous dysplasia (ESD, an ESCC precursor) (12), or ESCC (13) cases and controls. Additionally, periodontitis (a disease of oral dysbiosis) may be associated with increased esophageal cancer risk (14).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Porphyromonas gingivalis may serve as a biomarker of esophageal squamous cell carcinoma. According to Chen et al.,63 altered bacterial microbiota in the saliva is related to a higher risk of esophageal squamous cell carcinoma. The carriage of genera Lautropia, Bulleidia, Catonella , Corynebacterium , Moryella , Peptococcus and Cardiobacterium is lower in esophageal squamous cell carcinoma patients than in individuals without this cancer.…”
Section: Microbiome and Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…More studies are still needed to further understand the molecular mechanisms of the development of ESCC. Anyang, located in Henan Province of China, is one of the cities with the highest incidence and mortality of ESCC in China (Cheng et al, 2011). Every patient was matched with a control individual in terms of the gender and age (P=0.785).…”
Section: Discussionmentioning
confidence: 99%